Numerical investigation on the effect of Al2O3-water nanofluid on direct steam generation in parabolic trough collectors - Safari Chukami, Babak; Heyhat, Mohammad Mahdi (Applied thermal engineering, 2024)
[Display omitted] •Nanofluid flow boiling was simulated under uniform and non-uniform heat fluxes.•Al2O3-water based nanofluids with φ = 0 %, 1 %, 1.5 % and 2 % were considered.•The maximum Nu ratio of non-uniform to uniform heat fluxes was 544%.•Outlet vapor volume fraction was 3.13% more for non-uniform than uniform heat flux.•Average Nu decreased up to 21.24% when using nanofluid compared to pure water. The utilization of solar energy through direct steam generation (DSG) in parabolic trough collectors is a novel approach. In addition, due to higher thermophysical properties, the effect of using nanofluid as the coolant has been the subject of some of the recent studies but the applicability of the nanofluids in DSG process has not been studied before. In this study, the flow boiling of Al2O3 nanofluid at volume fractions 1%, 1.5% and 2%, under uniform and non-uniform heat fluxes has been studied numerically. The Eulerian model was used and non-equilibrium RPI was applied as the boiling model. The validation was done for flow boiling of pure water and Al2O3 nanofluid separately, with the available data in the literature. The results showed that the vapor volume fraction at the outlet is higher under non-uniform heat flux and adding nanoparticles would increase the vapor generation in the tube. Adding nanoparticles to the pure water increased the vapor volume fraction at the outlet up to about 8.64% in respect to pure water under uniform and non-uniform heat fluxes. The average Nu was up to 544% higher under non-uniform heat flux compared to uniform heat flux. Due to the presence of stratified flow, increasing nanofluid concentration reduced the average Nu up to 21.24% and 10.24% under uniform and non-uniform heat flux, respectively.